STUDI HADIS TEMATIK KLASIK DAN KONTEMPORER : (MODEL DAN KARAKTERISTIK) - Fahmi Andaluzi; Repa Hudan Lisalam; Abdul Fatah (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2025)
ABSTRACTThematic hadith represents one of the essential approaches in hadith studies, aiming to present a comprehensive understanding by compiling narrations according to specific themes. This paper seeks to illustrate the general design of both classical and contemporary thematic hadith studies in responding to the dynamics and needs of hadith scholarship from the era of codification to the contemporary period. Employing a qualitative method based on library research, this study examines classical and contemporary literature on thematic hadith. The findings reveal that the characteristics of hadith compilation vary across different periods. During the era of the Companions, compilation was primarily for personal documentation. In the era of official codification, in addition to focusing on the authenticity of the isnād, the dominant motivation for collecting hadith was practical needs within the framework of fiqh, which were categorized into multi-themed and mono-themed works. In contrast, the contemporary period is more oriented toward addressing contemporary phenomena. Moreover, contemporary thematic studies continue to evolve through the adoption of new approaches and are less rigidly boundto in-depth isnād analysis as in earlier periods. Nonetheless, the main conclusion of this study highlights that thematic hadith studies not only serve as an instrument for verifying and classifying various narrations but also function as a means to develop a more comprehensive conceptual framework with one primary goal: ensuring that the Prophet’s hadiths remain relevant and applicable across time and circumstance.Keywords: Thematic Hadith, Classical, Contemporary. ABSTRAKHadis tematik merupakan salah satu pendekatan penting dalam studi hadis yang bertujuan menyajikan pemahaman komprehensif dengan cara menghimpun riwayat berdasarkan tema tertentu. Tulisan ini ingin menggambarkan bagaimana desain umum studi hadis tematik klasik dan kontemporer dalam upaya merespons dinamika dan kebutuhan hadis dari masa kodifikasi hingga era kontemporer. Dengan menggunakan metode kualitatif berbasis studi kepustakaan, penelitian ini menelaah literatur hadis tematik klasik dan kontemporer. Hasil penelitian menunjukkan bahwa karakteristik pengumpulan hadis dari masa ke masa memiliki perbedaan. Pada masa sahabat, kompilasi hadis lebih kepada kebutuhan catatan pribadi, dan pada masa kodifikasi resmi, di samping fokus autentisitas sanad, motivasi pengumpulan hadis dominan didorong oleh kebutuhan praktis dalam nuansa fikih yang terbagi menjadi multitema dan monotema. Adapun pada masa kontemporer lebih berorientasi pada fenomena-fenomena kontemporer. Di samping itu, studi tematik kontemporer terus mengalami perkembangan seperti pengadopsian pendekatan-pendekatan baru, dan juga tidak terlalu terpaku pada analisis kualitas sanad secara mendalam sebagaimana pada masa awal kemunculannya. Namun, kesimpulan utama penelitian ini menunjukkan bahwa studi hadis tematik tidak hanya berfungsi sebagai instrumen verifikasi dan klasifikasi berbagai riwayat, tetapi juga menjadi sarana pengembangan kerangka konseptual yang lebih komprehensif dengan satu tujuan utama; bagaimana hadis-hadis Nabi saw. tetap relevan dan praktis di setiap waktu dan kondisi. Kata Kunci: Hadis Tematik, Klasik, Kontemporer.